The trick brain selections from the Tony and Elham Salamé Collection-Aïshti Foundation - Gioni, Massimiliano 1973-; Atkins, Ed 1982- (Skira, 2017)
"Taking its title from a video installation by Ed Atkins in the collection, The Trick Brain establishes new connections between works of Neo-Surrealist sensibility."--Publisher's website
Published on the occasion of the third exhibition of the Aïshti Foundation, Beirut, Lebanon, October 22, 2017
Keywords: Salamé, Tony; Salamé, Elham; Aïshti Foundation; Geschichte 1961-2017; Kunst; Sammlung; Art, Modern / 21st century / Exhibitions; Art, Modern / 20th century / Exhibitions; Art / Lebanon / Beirut / Exhibitions; Salamé, Tony / Art collections / Exhibitions; Salamé, Elham / Art collections / Exhibitions; Aïshti Foundation / Exhibitions; Exhibition catalogs; Ausstellungskatalog -- Aïshti Foundation -- 22.10.2017- -- Beirut; Bildband